O sistema do capital e os povos originários do Brasil: de quem é a questão? - Miranda, Thaís De Oliveira (2022)
The intensification of the violence perpetrated against the indigenous peoples in Brazil after the institutional coup of 2016 – especially during the Bolsonaro government –, substantiated in the invasions of their lands, in illegal occupation, in criminal burnings, in deforestation, and in all forms of dispossession, which have been taking place throughout the national territory, it is understood as a historical and dynamic process linked to the movement of production and reproduction of capital and, therefore, to the geographical expansion of capitalism and the continuous primitive accumulation of capital. In this sense, the apprehension of the contradictions inherent to the dialectical interaction between indigenous peoples and bourgeois society today necessarily permeates the understanding of the particularity of capitalist development in the Brazilian economic and social formation. The ontological approach allowed us to apprehend the historical and social foundations that found the construction of the term indigenous question, articulating it as an expression of the historical movement integrated to the totality. The capitalist mode of capitalist production and accumulation assume the annihilation of any mode of production that is not based on private ownership of the land, and on the non-exploitation of the human being by another human being, constituting the resistance of the original peoples to the rooting of capital the fundamental reason for the intermittent project of its extermination